PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BIOLOGI BERBASIS PROBLEM SOLVING PADA MATERI PENCEMARAN LINGKUNGAN KELAS VII SMP - Wazzaitun, Wazzaitun; Widiana, Rina; Sari, Liza Yulia (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ Student Worksheet is one sheet containing materials in which there is a summary of the material that is accompanied by a collection of exercises . With the LKS students are expected to understand the description of the subject matter provided by the teacher. Based on observations and interviews that have been conducted in SMP Muhammadiyah 6 Padang that in the second semester junior class VII using teaching materials such as worksheets, worksheets used in schools does not meet the learning objectives that are developed by teachers and worksheets used in schools only contains only a summary of the material and not equipped with an image.This research aims to generate worksheets based Problem Solving biological material environmental pollution on a valid and practical . Type of research is the development of the procedural model that aims to produce a product, the product is developed using 3 - D stage of Four Â models define phase , design , and develop .Research subjects of 5 people validator and 20 students. The research data is the primary data were analyzed by descriptive analysis. The result is the value obtained validity by faculty and teachers of 84,125 %, while the value of the practicalities of 86,87 % by teachers and by students of the value of the practicalities of 87,54 % . It can be concluded that the BLM has produced a valid and practical .Â